2022
DOI: 10.3389/fnmol.2022.1011225
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells for the treatment of Alzheimer’s disease: Strategies and limitations

Abstract: Alzheimer’s disease (AD) is a major cause of age-related dementia and is characterized by progressive brain damage that gradually destroys memory and the ability to learn, which ultimately leads to the decline of a patient’s ability to perform daily activities. Although some of the pharmacological treatments of AD are available for symptomatic relief, they are not able to limit the progression of AD and have several side effects. Mesenchymal stem/stromal cells (MSCs) could be a potential therapeutic option for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 155 publications
0
14
0
Order By: Relevance
“…However, this adaptive mechanism has a limit, and so when ROS’ homeostatic role is surpassed, this deteriorates cellular damage and, subsequently, the aging process [ 69 ]. Moreover, MSCs’ use has been proposed for the treatment of several diseases such as cardiovascular and neurodegenerative, and, as a result, they have a central role in regenerative medicine [ 70 , 71 , 72 ]. However, oxidative stress leads to MSCs’ death, and thus impairs their therapeutic effects [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this adaptive mechanism has a limit, and so when ROS’ homeostatic role is surpassed, this deteriorates cellular damage and, subsequently, the aging process [ 69 ]. Moreover, MSCs’ use has been proposed for the treatment of several diseases such as cardiovascular and neurodegenerative, and, as a result, they have a central role in regenerative medicine [ 70 , 71 , 72 ]. However, oxidative stress leads to MSCs’ death, and thus impairs their therapeutic effects [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…10 When treating AD with MSCs, MSCs proliferate astrocytes, metabolize glutamate and gamma-aminobutyrate, inhibit neural cell necrosis, and unleash growth factors (like brain-derived neurotrophic factor [BDNF]) to enhance neurogenesis by stimulating neural progenitor cells because of their antioxidant properties and antiapoptotic effects. 11,12 To stop additional tissue damage brought on by chronic neuroinflammation, MSCs also have modulatory effects on the immune system by bypassing or suppressing proinflammatory microglia (M1) activation and encouraging the activation of anti-inflammatory microglia (M2). Research has proven that MSCs can boost autophagy activation, which is likely to be the reason for the lysosomal clearance of Aβ plaques.…”
Section: Mesenchymal Stem Cells Applications In Admentioning
confidence: 99%
“…Irrespective of the neurodegenerative conditions discussed in this review, the limited efficacy observed in MSC treatment and the disparities between outcomes in mouse models and human clinical trials may be attributed to several factors. These include the specific source, culture, and isolation methods employed for MSCs, the dosage of transplanted cells, and the timing and route of delivery [ 195 , 196 , 197 , 198 , 199 , 200 ]. Furthermore, the accurate selection of patients and the identification of outcome measurements for assessing the success of MSC treatment are critical considerations that can significantly contribute to differences observed in clinical trials.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…While endogenous repair mechanisms and injected MSCs can work in synergy during the repair of active plaques in relapsing-remitting MS, progressive forms of the disease witness a reduction in the function of reparative cells due to gliosis and the formation of fibrotic scars [ 236 ]. Similarly, in AD and PD, despite promising preclinical data, most clinical trials involving MSCs have yielded disappointing results due to the pathological variability corresponding to different stages of the diseases [ 196 , 198 ]. This heterogeneity in disease stages and phases introduces considerable variability across trials, both in terms of the therapeutic windows (spanning from acute to chronic stroke stages) and the routes of administration [ 215 , 216 , 217 , 237 , 238 , 239 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%